2012
DOI: 10.1371/journal.pone.0046311
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Neutrophil Response Mediated by S100 Alarmins during Vaginal Candida Infections Is Independent of the Th17-Pathway

Abstract: Vulvovaginal candidiasis (VVC) caused by Candida albicans affects a significant number of women during their reproductive ages. Clinical observations revealed that a robust vaginal polymorphonuclear neutrophil (PMN) migration occurs in susceptible women, promoting pathological inflammation without affecting fungal burden. Evidence to date in the mouse model suggests that a similar acute PMN migration into the vagina is mediated by chemotactic S100A8 and S100A9 alarmins produced by vaginal epithelial cells in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 32 publications
6
76
0
2
Order By: Relevance
“…All protocols were approved by the Ethics Committee on the Use of Animals in Research -CEUA School of Pharmaceutical Sciences of Araraquara -UNESP (protocol number 34/2013 34 using a micropipette with disposable tips. On days 2, 6, and 10 after the infection, the vaginal load of C. albicans was evaluated through vaginal lavage with 0.1 mL of PBS, and the fungal count was determined by the CFU assay on sabouraud dextrose agar (SDA).…”
Section: Experimental Vvcmentioning
confidence: 99%
“…All protocols were approved by the Ethics Committee on the Use of Animals in Research -CEUA School of Pharmaceutical Sciences of Araraquara -UNESP (protocol number 34/2013 34 using a micropipette with disposable tips. On days 2, 6, and 10 after the infection, the vaginal load of C. albicans was evaluated through vaginal lavage with 0.1 mL of PBS, and the fungal count was determined by the CFU assay on sabouraud dextrose agar (SDA).…”
Section: Experimental Vvcmentioning
confidence: 99%
“…2) prior to the infection time, however in some infection times detectable changes in the cellular pattern of the sub mucosal layer were observed, possibly due to lack of fungi invasion in deeper structures, which could lead to more effective and diversified cellular immune response (Black et al, 1998;de Bernardis et al, 2000). Yano et al (2012) demonstrated an important polymorphonuclear role in the symptomatic VVC infection establishment, which seems to be related to alarmins production by the vaginal epithelial cells. These molecules are able to attract PMN and contribute to the acute VVC symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…VVC is an opportunistic infection that affects 75% of women during their reproductive life and about 5% of them will develop Recurrent Vulvovaginal Candidiasis (RVVC) (Fidel et al, 1995;Carrara et al, 2010;Harriott et al, 2010;Yano et al, 2012). The mechanism of defense used by the host against this fungus is related to an activity of innate and adaptive immune response (Yano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, SAP overexpression strains did not recruit more neutrophils than their isogenic empty vector control did. We previously identified the pleiotropic innate inflammatory cytokine IL-1␤ as a relevant biomarker of vaginal immunopathology and known effector of inflammasome activa- tion, a crucial host signaling pathway activated during murine VVC (4,6,(22)(23)(24)(25). Importantly, recombinant SAPs have also been demonstrated to activate the inflammasome and to liberate IL-1␤ in the vaginal epithelium (16,26,27).…”
Section: Resultsmentioning
confidence: 99%